Assessing the effectiveness of "intuitive" vibrotactile warning signals in preventing front-to-rear-end collisions in a driving simulator. - Ho, C; Reed, N; Spence, C (2006)
This study was designed to investigate the possibility that driver responses to potential front-to-rear-end collision situations could be facilitated by implementing vibrotactile warning signals that indicate the likely direction of the potential collision. In a car following scenario in a driving simulator, participants drove along a rural road while trying to maintain a safe headway distance to the lead car using a visual distance display. Participants had to respond as quickly as possible to the sudden deceleration of the lead car which had its brake lights disabled, either with or without vibrotactile cues (presented in different experimental blocks). The results demonstrated significantly faster braking responses and larger safety margins when the vibrotactile warning signal was presented than when it was not. These findings demonstrate the effectiveness of vibrotactile cues in helping drivers to orient their spatial attention in the appropriate direction. Our results add to a growing body of empirical evidence highlighting the potential benefits of using "intuitive" vibrotactile in-car displays, in this case, to alert drivers to potential collisions and to provide time-critical directional information.